2012
DOI: 10.7324/japs.2012.2629
|View full text |Cite
|
Sign up to set email alerts
|

Comparative toxicity of Butachlor, Imidacloprid andSodium fluoride on protein profile of the walking catfish Clarias batrachus

Abstract: Freshwater cat fish Clarias batrachus was exposed to Butachlor, Imidacloprid and Sodium fluoride with lethal and sub-lethal concentration for 72 hrs and 21 days durations. Protein changes in liver and muscles were analyzed after exposure period. Imidacloprid and sodium fluoride caused remarkable protein loss lethal concentration but at sub-lethal level their toxicity was moderate. But Butachlor caused remarkable protein loss at lethal as well as sublethal conentartion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Our results about dose dependent decrease in total protein observed might be due to counter mechanism against different toxicity sign occurred due to exposure of Imidacloprid and are in agreement with reports available in other model organisms studied like in Channa punctatus [40] and Quails [41]. Rajput et al [42] reported that Imidacloprid caused up to 49% protein loss at lethal concentration (4 ppm) in liver in walking fish and at sub-lethal dose (2 ppm) caused 27% protein loss. In contrary no changes in total protein reported in chicken [35] and rat [32] after Imidacloprid exposure.…”
Section: Discussionsupporting
confidence: 92%
“…Our results about dose dependent decrease in total protein observed might be due to counter mechanism against different toxicity sign occurred due to exposure of Imidacloprid and are in agreement with reports available in other model organisms studied like in Channa punctatus [40] and Quails [41]. Rajput et al [42] reported that Imidacloprid caused up to 49% protein loss at lethal concentration (4 ppm) in liver in walking fish and at sub-lethal dose (2 ppm) caused 27% protein loss. In contrary no changes in total protein reported in chicken [35] and rat [32] after Imidacloprid exposure.…”
Section: Discussionsupporting
confidence: 92%
“…While acute mortality of fish from the neonicotinoid insecticides is rare, Rajput et al. ( 2012 ) reported that imidacloprid was toxic to freshwater catfish, Clarias batrachus , when exposed for 21 days, but only at high doses. Protein loss was reported when exposed to high concentrations that later caused lethality.…”
Section: Fisheries and Aquaculturementioning
confidence: 99%
“…A study [17] also reported that the residues of butachlor in paddy field, even though lower than the safe concentration, caused toxic effect to Cyprinus carpio. In another study, butachlor was found to cause remarkable protein loss in Clarias batrachus at both lethal and sub-lethal concentration which might be due to increased proteolysis [18] or by metabolic utilization of ketoacids to glucogenesis pathway for synthesis of glucose [19]. The above results demonstrated adverse effects of butachlor on the normal reproductive process of zebra fish and also found to disrupt the thyroid and sex steroid endocrine systems when exposed to butachlor for 30 days [20].…”
Section: Discussionmentioning
confidence: 90%